Impact of Macroeconomic Factors on Nationwide Supply Chain Performance - Ahmad Hidayat; Mohammad Mulyadi; Paisal Halim; Dwi Purwoko (International Journal of Supply Chain Management, 2020)
Abstract- The objective of this study is to investigate the role of macroeconomic factors in the supply chain. “Therefore, this study examined the role of  GDP growth rate, the degree of openess, the rate of exchange and balance of payment effect on foreign direct investment (FDI) and FDI effect on the supply chain. In this study, data were collected from Indonesian economists. Email addresses of Indonesian economists were collected and email was sent to them to get responses. Only one hundred email addresses were found of various economists. Therefore, the total sample size was one hundred. From total one hundred, sixty economists responded. Outcomes of the study show that increases in GDP growth rate, the degree of openness and balance of payment increases the nationwide supply chain performance. Decreases in GDP growth rate, the degree of openness and balance of payment decreases the nationwide supply chain performance”. However, increases in the rate of exchange decrease the FDI growth rate which ultimately decreases the supply chain practices.